2006
DOI: 10.1121/1.2202909
|View full text |Cite
|
Sign up to set email alerts
|

A stable boundary element method for modeling transient acoustic radiation

Abstract: Transient acoustic radiation from a closed axisymmetric three-dimensional object is modeled using the time domain boundary element method. The widely reported instability problems are overcome by reformulating the integral equation to obtain a Burton and Miller type equation in the time domain. The stability of such an approach is mathematically justified and supported by subsequent numerical results. The hypersingular integrals which arise are evaluated using a method valid for any surface discretization. Num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 16 publications
2
51
0
1
Order By: Relevance
“…In this work we adopt the second approach with a view to the future development of methods for reducing the storage complexity and setup time related to those discussed above. Applying the trapezoidal rule to (54) yields (10); hence, we define A m (s) = s −m A(s) for some m 2 and instead evaluateŵ n ( t, A m ). In order to obtain an approximation of the layer density , we must replace the data f (·, t) ∈ H −1/2 ( ), t ∈ (0, T ), with a function g(·, t) ∈ H −1/2 ( ) where f is given by the mth time derivative of g, f = g (m) , and…”
Section: Theorem 42mentioning
confidence: 99%
“…In this work we adopt the second approach with a view to the future development of methods for reducing the storage complexity and setup time related to those discussed above. Applying the trapezoidal rule to (54) yields (10); hence, we define A m (s) = s −m A(s) for some m 2 and instead evaluateŵ n ( t, A m ). In order to obtain an approximation of the layer density , we must replace the data f (·, t) ∈ H −1/2 ( ), t ∈ (0, T ), with a function g(·, t) ∈ H −1/2 ( ) where f is given by the mth time derivative of g, f = g (m) , and…”
Section: Theorem 42mentioning
confidence: 99%
“…The CFIE therefore permits sound emanating from the obstacle model to return to the medium, but discretises sound arriving from the medium, passing that data to the obstacle model and scattering cancelling waves into Ω − . As a side effect of this, it also permits any small amounts of energy entering Ω − due to only approximate cancellation of incident and scattered waves to exit into Ω + without reflection, hence internal cavity resonances do not occur 12 . It would be desirable to create a variant of the CFIE which is valid for a more general class of waves; in this paper we are specifically interested in plane waves travelling in the direction ‫ܓ‬ ܽ,݉ ,݊ .…”
Section: Figure 2 Conceptual Separation Of Medium and Obstacle Modelsmentioning
confidence: 99%
“…More generally, it has been shown that when 0<α<1 energy flows out of the cavity and it cannot support resonant modes 15 . Consequently, the application of L c has been shown to grant superior stability to L p and L v for a variety of test geometries.…”
Section: Combined Field Integral Equation Operatormentioning
confidence: 99%
“…The dominant mathematical analysis of this phenomenon is the Singularity Expansion Method (SEM) 20,21,22 which expands the continuous time system response into a sum of damped exponentials with poles s n and corresponding spatial modes Φ n : [15] where Φ i (t) represents system excitation. This can be written in discrete time as:…”
Section: Bem Stability Analysismentioning
confidence: 99%